2015
DOI: 10.1016/j.radonc.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

A new CT-based method to quantify radiation-induced lung damage in patients

Abstract: A new method to assess radiation-induced lung toxicity (RILT) using CT-scans was developed. It is more sensitive in detecting damage and corresponds better to physician-rated radiation pneumonitis than routinely-used methods. Use of this method may improve lung toxicity assessment and thereby facilitate development of more accurate predictive models for RILT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…Quantification of lung density changes has been investigated for patient-specific susceptibility of radiation-induced lung damage following SABR [64]. A recent study by Ghobadi et al [65] showed that the combination of mean density changes with the standard deviation of the density was a more sensitive and specific method to assess radiationinduced lung damage than measuring differences in mean density. Predictive modelling of radiation pneumonitis using texture analysis on CT has been studied following definitive radiation for lung and esophageal cancer [66,67].…”
Section: Sensitivity (%) Specificity (%)mentioning
confidence: 99%
“…Quantification of lung density changes has been investigated for patient-specific susceptibility of radiation-induced lung damage following SABR [64]. A recent study by Ghobadi et al [65] showed that the combination of mean density changes with the standard deviation of the density was a more sensitive and specific method to assess radiationinduced lung damage than measuring differences in mean density. Predictive modelling of radiation pneumonitis using texture analysis on CT has been studied following definitive radiation for lung and esophageal cancer [66,67].…”
Section: Sensitivity (%) Specificity (%)mentioning
confidence: 99%
“…We accounted for the massive multiple comparison (MC) problem, which may arise in the analysis of imaging data when the statistical analysis is run separately for each voxel, by applying nonparametric procedures based on randomization/permutation testing (6). Whereas imaging-based methods have been developed to measure individual patient reactions to lung irradiation (710), we are unaware of studies that apply this approach to explore the lung dosimetric patterns associated with RILD.…”
Section: Introductionmentioning
confidence: 99%
“…Our imaging biomarkers are novel. Other groups have proposed methods using feature analysis and deformable image registration to score parenchymal change characteristic of acute RILD (i.e., radiation pneumonitis) [34][35][36]. This methodology is less applicable to chronic RILD due to the increased complexity of thoracic anatomical change.…”
Section: Discussionmentioning
confidence: 99%